PENGARUH PENGGUNAAN MEDIA DIORAMA TERHADAP PENGENALAN LIFE SCIENCE (METAMORFOSIS) PADA ANAK USIA 5-6 TAHUN DI TK PUSPITA WULANDARI MUARO JAMBI - Riska Aulia Putri; Rizki Surya Amanda; Akhmad Fikri Rosyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using diorama media on children’s introduction to life science (metamorphosis) in children aged 5-6 years at TK Puspita Wulandari Muaro Jambi. This research used a quantitative approach with a quasi-experimental design, specifically a Nonequivalent Control Group Design. The sample consisted of two classes, namely class B1 as the experimental group with 10 children and class B2 as the control group with 8 children. The data collection technique used observation, while data analysis included normality test, homogeneity test, and hypothesis testing using an independent sample t-test. The results showed that the use of diorama media had an effect on improving children’s life science abilities. This is evidenced by the mean posttest score of the experimental group (35.5), which was higher than the control group (19.9). The hypothesis testing results showed a significance value of 0.03 < 0.05, meaning that H₀ was rejected and Hₐ was accepted. Therefore, diorama media has a significant effect on children’s introduction to life science (metamorphosis) in children aged 5-6 years.